Precursors to Social and Communication Difficulties in Infants At-Risk for Autism: Gaze Following and Attentional Engagement. - Bedford, Rachael; Elsabbagh, Mayada; Gliga, Teodora; Pickles, Andrew; Senju, Atsushi; Charman, Tony; Johnson, Mark (Journal of Autism & Developmental Disorders, 2012)
Whilst joint attention (JA) impairments in autism have been widely studied, little is known about the early development of gaze following, a precursor to establishing JA. We employed eye-tracking to record gaze following longitudinally in infants with and without a family history of autism spectrum disorder (ASD) at 7 and 13 months. No group difference was found between at-risk and low-risk infants in gaze following behaviour at either age. However, despite following gaze successfully at 13 months, at-risk infants with later emerging socio-communication difficulties (both those with ASD and atypical development at 36 months of age) allocated less attention to the congruent object compared to typically developing at-risk siblings and low-risk controls. The findings suggest that the subtle emergence of difficulties in JA in infancy may be related to ASD and other atypical outcomes.